The Rhetorical Evolution of the Minimum Wage - Oren M. Levin-Waldman (Levy Economics Institute of Bard College, 1999)
The concept of the minimum wage has undergone several rhetorical permutations. Originally conceived as a living wage, which would function as a family wage, it ultimately became a matter of macroeconomic policy, the goals of which were to achieve greater efficiency and in some case economic development. In recent years, the rhetoric has narrowed to a debate that pits a youth disemployment effect against assisting the poor. This paper traces the rhetorical evolution of the minimum wage and shows how the rhetoric employed by various groups has been shaped by the specifics of the political and economic environment.
Keywords: 330